2021
DOI: 10.48550/arxiv.2109.11535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circularly polarized radio emission from the repeating fast radio burst source FRB 20201124A

Pravir Kumar,
Ryan M. Shannon,
Marcus E. Lower
et al.

Abstract: The mechanism that produces fast radio burst (FRB) emission is poorly understood. Targeted monitoring of repeating FRB sources provides the opportunity to fully characterise the emission properties in a manner impossible with one-off bursts. Here we report observations of the source of FRB 20201124A, with the Australian Square Kilometre Array Pathfinder (ASKAP) and the Ultra-wideband Low (UWL) receiver at the Parkes 64-m radio telescope (Murriyang). The source entered a period of emitting bright bursts during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 71 publications
(142 reference statements)
0
23
0
Order By: Relevance
“…The recently reported circular polarisation in the repeating FRB 20201124A can reach a fraction up to 75% (Hilmarsson et al 2021;Kumar et al 2021;Xu et al 2021). According to the calculations in the previous section, a general picture for the circular polarisation in FRBs is shown in Figure 6.…”
Section: Implications For Frb Circular Polarisationmentioning
confidence: 58%
See 2 more Smart Citations
“…The recently reported circular polarisation in the repeating FRB 20201124A can reach a fraction up to 75% (Hilmarsson et al 2021;Kumar et al 2021;Xu et al 2021). According to the calculations in the previous section, a general picture for the circular polarisation in FRBs is shown in Figure 6.…”
Section: Implications For Frb Circular Polarisationmentioning
confidence: 58%
“…Previously, circular polarisation is reported in FRB 181112 (Cho et al 2020, circular polarisation fraction up to 34%), and in FRB 190611 (Day et al 2020, circular polarisation fraction of one subpulse up to 57%). Recently, significant circular polarisation is reported in one repeating FRB 20201124A (Hilmarsson et al 2021;Kumar et al 2021;Xu et al 2021). The circular polarisation fraction can be as high ⋆ E-mail: tonghao@gzhu.edu.cn as 75% (Xu et al 2021), which is very high even compared with that of pulsars and magnetars (Dai et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another active repeater FRB 20201124A (Lanman et al 2021;Kumar et al 2021;Nimmo et al 2021;Hilmarsson et al 2021) is found in a Milky-Way-sized, metal-rich, barred-spiral host galaxy at z = 0.098 (Xu et al 2021;Fong et al 2021;Ravi et al 2021;Piro et al 2021). This repeater indicates a significant, irregular, variation of the Faraday rotation over 36 days.…”
Section: Introductionmentioning
confidence: 92%
“…This repeater indicates a significant, irregular, variation of the Faraday rotation over 36 days. Some bursts appear to have circular polarization up to 75% (Kumar et al 2021;Xu et al 2021). In particular, the frequency spectra of both circular polarization and linear polarization of some bursts with moderate circular polarization show clear oscillating structures (Xu et al 2021), which might originate from the polarized absorption or Faraday conversion mechanism (Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%